Warm-up strategies in freestyle snowsports: Effects of extremely cold environments on performance - Crowhen, S. (Auckland University of Technology, 2018)
Background: The implementation of a dynamic warm-up is a widely accepted practice amongst athletes in many sports, but less common in freestyle snow sports (i.e. skiing and snowboarding). Moreover, in freestyle skiing and snowboard there are extended periods (transition phase = 10 to 15 min) of time following the warm-up where athletes are inactive and exposed to extremely cold temperatures (-30 to -10 o C). These transition periods exacerbate the issue of maintaining body temperature and physical readiness in the extreme cold. The literature regarding the effectiveness of a warm-up and its residual benefits during transition phases in cold temperatures is limited. Purpose: To examine the effects of a neuromuscular warm-up (NWU), dynamic re-activation (RA), and passive re-warming (PRW) on squat jump (SJ) in snow sport athletes under extremely cold environmental conditions. Methods: Nine freestyle snow sport athletes (age = 21.1 ± 5.0 years; Mean ± SD) volunteered to participate in this study. A randomised repeated measures cross-over design was used. Following the completion of a standardised NWU, participants sat inactive in a temperature controlled industrial freezer (-20 to -18 o C) wearing cold weather training clothing. At specified time points, participants completed a vertical SJ protocol as the performance measure. The participants completed both experimental conditions (RA or PRW) on separate occasions, where they performed a dynamic RA or PRW, 20 min following the NWU. Five SJ were performed at the following time points: 14 min (4 min post NWU), 18 min (8 min post NWU), 26 min (16 min post NWU), 39 min (4 min post RA or PRW), 43 min (8 min post RA or PRW), and 51 min (16 min post RA or PRW). Results: Jump height (JH), peak force (PF) and impulse (IMP) showed excellent inter-day reliability (ICC > 0.80; CV < 5.3 %) and were used to assess jump performance across the two conditions. Small to moderate significant reductions in JH (ES > 0.2; P < 0.10) were observed at 26 min, 39 min, 43 min and, 51 min of cold exposure time under both conditions. Small significant reduction in PF (ES > 0.2; P < 0.10) were also observed at 51 min in both conditions. JH and PF decreased by 9 % and 5 %, respectively following 51 min of cold exposure. Small significant differences (ES > 0.2; P < 0.10) were observed between the PRW and RA at 4 min and 8 min post. The RA protocol had a likely beneficial effect on JH at these time points. Discussion: Participants had varying individual responses to the RA with some experiencing improvements in JH (6 to 12 %), while other had a poor response to RA, and JH continued to decline (0 to -7 %). A NWU appears insufficient to combat the effects of cold exposure during transition phases where athletes are inactive for short periods of time (4 to 16 min). The implementation of RA strategies may reduce the negative impact of cold by increasing tissue temperature and providing a post activation potentiation (PAP) stimulus. However, RA protocols need to be individualised, as negative or negligible responses may occur in some athletes. It is likely that decreasing muscle temperature plays a significant role in the decline JH and PF.